The In Vitro and In Vivo Synergistic Antimicrobial Activity Assessment of Vacuum Microwave Assisted Aqueous Extracts from Pomegranate and Avocado Fruit Peels and Avocado Seeds Based on a Mixtures Design Model - Prodromos Skenderidis; Stefanos Leontopoulos; Konstantinos Petrotos; Chrysanthi Mitsagga; Ioannis Giavasis (Plants, 2021)
The present study aimed to assess the antimicrobial properties of encapsulated lyophilized powdered extracts of pomegranate peels (PP), avocado peels (AP) and avocado seeds (AS) in vitro and in vivo. Minimum Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) methods, optical density measurement, and well diffusion assay were used to determine antimicrobial activity against food borne bacteria (Gram− Escherichia coli, Salmonella typhimurium, Campylobacter jejuni, Pseudomonas putida), (Gram+ Staphylococcus aureus, Listeria monocytogenes, Clostridium perfringens, Lactobacillus plantarum), and fungi (Penicillium expansum and Aspergillus niger) based on a mixture design model. Additionally, the most effective powder was studied in vivo in yogurt, cream cheese, and minced meat burger. The samples that contained high polyphenol content also exhibited higher antioxidant, antimicrobial, and antifungal activity. From the results of the well diffusion, the MIC/MBC, and the cell optical density assays, the antimicrobial activity of the extracts was found to be correlated to the total phenolic content (TPC) of the samples and the type of the microorganism. The pomegranate peels extract presented the higher TPC and antioxidant activity and constitute the highest percentage in the most active antimicrobial mixture. The powders that were tested in vitro showed microbial type-dependent effects in each food model. The results presented here can be further studied in the large-scale industrial production of natural food preservatives.